2010
DOI: 10.1128/iai.00192-10
|View full text |Cite
|
Sign up to set email alerts
|

A Francisella tularensis Live Vaccine Strain (LVS) Mutant with a Deletion in capB , Encoding a Putative Capsular Biosynthesis Protein, Is Significantly More Attenuated than LVS yet Induces Potent Protective Immunity in Mice against F. tularensis Challenge

Abstract: Francisella tularensis, the causative agent of tularemia, is in the top category (category A) of potential agents of bioterrorism. The F. tularensis live vaccine strain (LVS) is the only vaccine currently available to protect against tularemia; however, this unlicensed vaccine is relatively toxic and provides incomplete protection against aerosolized F. tularensis, the most dangerous mode of transmission. Hence, a safer and more potent vaccine is needed. As a first step toward addressing this need, we have con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 52 publications
4
83
0
1
Order By: Relevance
“…We also observed that vaccination doses as low as 200 to 500 CFU were completely protective against a challenge dose of 5.1 ϫ 10 3 CFU. This is important to note, since many of the strains previously reported to be attenuated and protective either were not challenged with such a high dose, required a higher vaccination dose, or required multiple vaccinations to achieve the same level of protection (15,16,18,20,26,30,32,36). There has been one other LVS mutant reported to provide full protection against an LVS challenge of 10 5 CFU with a vaccination dose of only 10 3 CFU (37).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that vaccination doses as low as 200 to 500 CFU were completely protective against a challenge dose of 5.1 ϫ 10 3 CFU. This is important to note, since many of the strains previously reported to be attenuated and protective either were not challenged with such a high dose, required a higher vaccination dose, or required multiple vaccinations to achieve the same level of protection (15,16,18,20,26,30,32,36). There has been one other LVS mutant reported to provide full protection against an LVS challenge of 10 5 CFU with a vaccination dose of only 10 3 CFU (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, no poly-D-glutamic acid has been identified in Francisella. Although Francisella capB mutants are attenuated during murine infection, an LVS capB mutant did not exhibit increased sensitivity to serum (110,213). Furthermore, it is not known whether CapB is required for production of the O-antigen capsule, the glycoprotein capsule-like complex, or a different bacterial envelope structure.…”
Section: Complement and Antibodymentioning
confidence: 99%
“…Interestingly, the Francisella genome is known to contain an operon with similarity to the Bacillus species capBCA genes necessary for the production of a poly-D-glutamic acid capsule (71,110,153). However, to date, no poly-D-glutamic acid has been identified in Francisella.…”
Section: Complement and Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent efforts to develop a tularemia vaccine have focused on live attenuated vaccines using site-specific deletion of virulence genes (3,(19)(20)(21)(22)(23)(24)(25)(26)(27). Studies have identified a number of mutations that attenuate F. tularensis to various degrees.…”
mentioning
confidence: 99%